mTOR Links Environmental Signals to T Cell Fate Decisions - Chapman, Nicole M.; Chi, Hongbo (Frontiers in Immunology, 2015)
T cell fate decisions play an integral role in maintaining the health of organisms under homeostatic and inflammatory conditions. The localized microenvironment in which developing and mature T cells reside provides signals that serve essential functions in shaping these fate decisions. Among these signals are those derived from the immune compartment, including antigens, costimulation, and cytokines, and systemic factors, including growth factors and nutrients. The mechanistic target of rapamycin (mTOR), a vital sensor of signals from within the immune microenvironment, and is a central regulator of T cell biology. In this review, we discuss how various environmental cues tune mTOR activity in T cells, and summarize how mTOR integrates these signals to influence multiple aspects of T cell biology.